FAKTOR-FAKTOR YANG MEMPENGARUHI PENCIPTAAN KEMAKMURAN DALAM MERGER DAN AKUISISI - Norhamida, Hana (Jurnal Organisasi dan Manajemen, 2006)
One of the company strategies to remain existing and developing in the creating of wealth as by merger and acquisition. Researchs say that some factors may influence it. This paper will explain some factors that may influence the wealth-creation for stock holder of acquisitor/bidder and target firm. The measurement of wealth used by public company do not require any financial statement analysis like measurement of value creation performance, because measurement of wealth rely on stocks market. The wealth-creation in the merger and acquisition transaction through abnormal return may be influenced by many factors as the following: acquisition type, form of payment, quantity of bidder, level of diversification, ownership distribution, management performance, firm size, and regulation.  acquisition, merger, wealth-creation.